2018
DOI: 10.1108/et-09-2017-0141
|View full text |Cite
|
Sign up to set email alerts
|

Internationalisation strategy, faculty response and academic preparedness for transnational teaching

Abstract: Transnational education (TNE), interpreted as the mobility of education programmes and providers between countries, has grown exponentially as a worldwide phenomenon in recent years. Higher education institutions (HEIs) have mainly used such opportunities to internationalise their degrees and programmes, and have paid scant attention on preparing academics to teach cross-culturally. As a result, academics being at the coalface of teaching and learning often feel under-informed, under-supported, underprepared, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…A research in 92 universities in the UK stated that, 'universities should strategically plan and firmly committed towards providing training of transactional teaching to the faculty members so as to make them competitive to deal with students belonging to different cultural backgrounds' (Nawaz, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A research in 92 universities in the UK stated that, 'universities should strategically plan and firmly committed towards providing training of transactional teaching to the faculty members so as to make them competitive to deal with students belonging to different cultural backgrounds' (Nawaz, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Professional growth and training can improve their grasp of inclusive teaching, cultural understanding, and aiding diverse students. This continuous backing promotes a more inclusive learning atmosphere in TNE programmes (Nawaz, 2018).…”
Section: Inclusive Learning Environment In Transnational Educationmentioning
confidence: 96%
“…To date, this aspect receives little recognition, even in established host countries. Nawaz (2018) investigated transnational teaching strategies by analyzing a United Kingdom's (UK) post-1992 university's documents of internationalisation strategy, annual reports, staff training and development programs etc. for the period between 1999 and 2016, and interviewing 11 stakeholders consisting academic staff member, educational developers and professionals services staff members.…”
Section: The Urgency Of Teacher Icc Training and Learningmentioning
confidence: 99%
“…for the period between 1999 and 2016, and interviewing 11 stakeholders consisting academic staff member, educational developers and professionals services staff members. His study found that the faculty members at the university lacked the knowledge and skills needed for effective pedagogical teaching, and there was less interest at the university or faculty level in ensuring that faculty members received appropriate training before departing for international teaching assignments (Nawaz, 2018).…”
Section: The Urgency Of Teacher Icc Training and Learningmentioning
confidence: 99%